Adolescent COVID-19-Associated Fatal Rhabdomyolysis. (December 2020) - Anwar, Huda; Al Lawati, Anwaar
Coronavirus disease 2019 (COVID-19) has become an urgent global health priority. Although most patients with COVID-19 manifest with fever and respiratory tract symptoms, COVID-19 infections may also involve other organs and extrarespiratory manifestations, including cardiac, gastrointestinal, hepatic, renal, and neurological symptoms. This case describes a 16-year-old boy who presented with fever, sore throat, myalgia, and subsequently with shortness of breath. A diagnosis of COVID-19 was confirmed by polymerase chain reaction. His condition deteriorated and he died within 3 days of admission. An evaluation of his past medical history confirmed an episode of viral illness which had progressed to myositis and rhabdomyolysis 1 year prior. Clinicians should be aware of this complication and maintain a high index of suspicion in cases of COVID-19 presenting with extrapulmonary symptoms.